STRATEGI PEMBELAJARAN PENDIDIKAN LUAR SEKOLAH - Bertha Bintari Wahyujati (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2006)
Instructional strategy is one of important factors to achieve instructional objectives. The instructional strategy developed for a teaching and learning situation will be effective if instructional methods and models are appropriately selected. This article discusses some considerations upon the selection of appopriate instructional strategies and describes a case study in life skills training. The case proves the significant role of appropriate instructional strategies in achieving training objectives.